Blood Feeding Insect Series: American Trypanosomiasis - Chagas Disease - Kevin Kobylinski; Roxanne Rutledge-Connelly (EDIS, 2006)
ENY-726, a 4-page illustrated fact sheet by Kevin Kobylinski and Roxanne Rutledge Connelly, describes this potentially fatal, chronic disease and the triatomine bugs that transmit it. It discusses the low risk of contracting the disease in Florida or from contaminated blood, and information on control measures. Includes references. Published by the UF Department of Entomology and Nematology, July 2006.